Fine ceramics (advanced ceramics, advanced technical ceramics). Mechanical properties of ceramic composites at ambient temperature in air atmospheric pressure. Determination of the resistance to crack propagation by notch sensitivity testing. (21st September 2022) - British Standards Institution,
No abstract available